“LA LECTURA DE PICTOGRAMAS EN EL DESARROLLO DEL LENGUAJE ORAL, EN LOS NIÑOS DE 4 AÑOS DEL CENTRO DE EDUCACIÓN INICIAL MARÍA GUERRERO VASQUEZ, DEL CANTÓN CHAMBO EN EL PERÍODO SEPTIEMBRE 2018 - JUNIO 2019”. - Chulli Cargua, Nancy Roxana (2019)
The research project determines the incidence of pictogram reading in the development of oral language in four-year-old children of the “María Guerrero Vásquez” Initial Education Center of the Chambo canton, in September 2018 - June 2019. Taking into account that pictograms are representations of a schematic sign. The name is called the signs of the alphabetic system, which were based using significant spellings that benefit language development. It means learning to use a code of symbols, which includes the acquisition of vocabulary, knowledge of the meaning of words, and an adequate elaboration of the sentences. The research had a non-experimental, descriptive, and field design. The population was the children of the “María Guerrero Vásquez” Initial Education Center. The sample was non-probabilistic and intentional and was determined with 21 children. The technique was the observation and the instrument the observation sheet through which it was a possible conclusion that the strategies are favorable for the development of oral language. The use of pictograms is fundamental in the children stage. It is viable for the development of their creativity because it stimulates their imagination, participation, identification of graphics, repetition of words, and acquisition of new words. it recommends that both teachers and parents use these new strategies to develop oral language like reading pictograms, favoring their significant learning and acquisition of new vocabulary in the classroom.